Inventory of Butterfly (Lepidoptera: Rhopalocera) at Agrotechno Park The University of Jember - Purwatiningsih, P.; Anggreini, Widyantari; Setiawan, Rendy (Universitas Jember, 2022)
The exploration of the butterfly on The University of Jember has been conducted. The objective of this study is to explore the diversity of butterfly on UPT Agrotechno Park The University of Jember. The research has been done during August to September 2020. Sampling was carried out by scanning methods in the fields with sweeping net. The results revealed the existence of 18 genus with four belonging to the families Papilionidae, Pieridae, Nymphalidae, and Lycaenidae. Moreover 24 species had been identified namely Papilio sp. 1, Papilio sp. 2, Troides sp., Graphium sp., Appias sp., Catopsilia sp., Delias sp. 1, Delias sp. 2, Eurema sp.1, Eurema sp. 2, Leptosia sp., Euthalia sp. 1, Euthlia sp. 2, Dophla sp., Elymnias sp., Euploea sp. 1, Euploea sp. 2, Hypolimnas sp., Junonia sp. 1, Junonia sp 2, Discophora sp., Acraea sp., Zizina sp. dan Lampides sp. Butterflies use plants as host plants and food plants. High host plant diversity is directly proportional to the diversity of butterfly species. The UPT Agrotechnopark Universitas Jember has 1 hectare of land in which there are collections of fruit, vegetable, ornamental, medicinal and food plants. The high diversity of host and forage plants in the UPT Agrotechnopark is a good habitat for butterflies. However, identification to the species taxa are further needed.